Recent impacts of anthropogenic climate change on a higher marine predator in western Britain - Riou, Samuel; Gray, Catherine M.; Brooke, M. de L.; Quillfeldt, Petra; Masello, Juan F.; Perrins, Christopher; Hamer, Keith C.; Justus Liebig University Giessen (My University, 2011)
Impacts of anthropogenic climate change on marine ecosystems are now widely acknowledged. In the NE Atlantic, abundant evidence from the partly enclosed waters of the North Sea indicates that recent climate-induced changes in primary and secondary productivity have been propagated up the food chain, with marked consequences for higher vertebrate predators such as seabirds. In contrast, however, there is much less indication of such impacts on higher predators in the more open Atlantic waters around the west coast of the British Isles. Through an annual comparison of chick growth and adult food provisioning behaviour of Manx shearwaters in SW Wales, we found that birds bred later and chicks attained lower peak and fledging masses in 2007 and 2008 than in any previous recorded year dating back to 1965. These changes were accompanied by a reduction in parental attendance at the colony, which was probably the result of parents switching to a dual foraging strategy in 2007 and 2008. These events were linked to higher sea surface temperature in the preceding winter and to a reduction in prey quality, as indicated by the mean body mass of 2 yr old herring. These are the first such findings for the west coast of Britain and indicate that within the NE Atlantic region, adverse impacts of climate change on higher marine predators are no longer restricted to the vicinity of the North Sea.
Keywords: Breeding success; Foraging behaviour; Global warming; Manx shearwater; Phenology; Sea surface temperature; ddc:570